Efficacy testing of an immersion vaccine against Aeromonas salmonicida and immunocompetence in ballan wrasse (Labrus bergylta, Ascanius). Issue 121 (February 2022) - Papadopoulou, Athina; Monaghan, Sean J.; Bagwell, Nicola; Alves, Mickael Teixeira; Verner-Jeffreys, David; Wallis, Tim; Davie, Andrew; Adams, Alexandra; Migaud, Herve
Abstract: The development of effective vaccines is a critical step towards the domestication of emerging fish species for aquaculture. However, traditional vaccine delivery through intraperitoneal (i.p.) injection requires fish to reach a minimum size and age and therefore cannot provide protection at early developmental stages when infection may occur. This study investigated the effectiveness of immersion vaccination with respect to immunocompetence in a cleaner fish species (ballan wrasse, Labrus bergylta, Ascanius) used in Atlantic salmon farming as an alternative means to control sea lice. The species is susceptible to atypical strains of Aeromonas salmonicida (a As ) at early life stages (<15 g), when i.p. vaccination is not applicable. While immersion vaccination is currently used in commercial hatcheries, the optimal fish size for vaccination, and efficacy of the vaccine delivered by this route has not yet been established. Importantly, efficacy depends on the capability of the species immune system to recognise antigens and process antigens to trigger and produce an adaptive immune response, (process known as immunocompetence). In this study, the efficacy of a polyvalent autogenous vaccine administered by immersion in juvenile ballan wrasse and the subsequent immune response induced was investigated after prime and booster vaccination regimes. In addition, temporal expression (0–150 days post hatch) of adaptive immune genes including major histocompatibility complex (MHC II CD74 molecule) and immunoglobulin M (IgM) was assessed using quantitative PCR (qPCR). Prime and/or boost vaccination by immersion of juvenile ballan wrasse (0.5 g and 1.5 g corresponding to 80 and 170 days post hatch (dph), respectively) did not provide significant protection against a As vapA V after bath challenge under experimental conditions. Despite no evident protection >80 dph, MHC II and IgM transcripts were first reported at 35 and 75 dph, respectively, suggesting a window of immunocompetence. The results provide important new information on the onset of adaptive immunity in ballan wrasse and highlight that immersion vaccination in the species for protection against a As should be performed at later developmental stages (>1.5 g) in the hatchery. Highlights: Autogenous vaccine offers no protection in farmed ballan wrasse at 0.5–1.5 g against atypical Aeromonas salmonicida vapA V. Immersion vaccination for a As should be performed at bigger sizes >1.5 g. Onset of adaptive immune genes responses reported for first time. MHC II and IgM transcript were first reported at 35 and 75 days post hatch.